RP-HPLC/MS-APCI analysis of odd-chain TAGs from Rhodococcus erythropolis including some regioisomers - Rezanka, Tomás; Schreiberová, Olga; Krulikovská, Tereza; Masák, Jan; Sigler, Karel (Chemistry and physics of lipids, 2010)
We used reversed phase liquid chromatography-atmospheric pressure chemical ionization mass spectrometry (RP-HPLC/MS-APCI) for direct analysis of triacylglycerols (TAGs) from four different cultivations of Rhodococcus erythropolis CCM 2595. This technique enabled us to identify and quantify the specific molecular species of TAGs directly from lipid extracts of the bacterium, including the determination of their basic characteristics such as retention time and mass spectra. A total of 17 TAGs having at least one odd-numbered-chain FA (fatty acid) were found. This is the first time when odd-chain TAGs, predominantly with pentadecanoic, margaric, and margaroleic acids, were identified. Multiple linear regression analyses were used for predicting retention times of molecular species, predominantly of odd-chain TAGs. Cultivations on two different substrates at two different temperatures (20 and 30 degrees C) showed that only temperature had any effect on the content of TAGs. In cultivations with succinate as a carbon source the content of these TAGs increased by half (i.e., from 23.5 to 34.2%) when the cultivation temperature was lowered from 30 to 20 degrees C. The content of the PoPoMo, PoMoO and PPoMo (see Table 1) TAGs containing the odd-numbered-chain margaroleic acid rose from 0.0 to 7.1% while in cultivation on phenol as a carbon source the lowering of cultivation temperature caused an increase of these TAGs from 0.5 to 6.7%.
Keywords: chromatografie kapalinová; Isomerism; Spectrometry, Mass, Electrospray Ionization; Species Specificity; hmotnostní spektrometrie s elektrosprejovou ionizací; Rhodococcus; isomerie; Triglycerides; druhová specificita; Chromatography, Liquid; triglyceridy